DECENTRALIZATION AS THE BASIS OF LOCAL SELF-GOVERNMENT - Tatyana Pupysheva (Research Retrieval and Academic Letters, 2023)
Since gaining independence, large-scale socio-economic and political transformations have been taking place in Kazakhstan, the decentralization of public administration and the development of local self-government institutions have been implemented. In this article, the author considers the types of decentralization and the reasons for its implementation. The main approaches to decentralization are described. In addition, the author analyzed the features of decentralization in the Republic of Kazakhstan, its positive and negative consequences, as well as the impact on the development of local self-government.